2012
DOI: 10.1007/s11940-012-0201-x
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Therapeutic Hypothermia

Abstract: Therapeutic Hypothermia has proven neuroprotective effects in global cerebral ischemia. Indications for hypothermia induction include cardiac arrest and neonatal asphyxia. The two general methods of induced hypothermia are either surface cooling or endovascular cooling. Hypothermia should be induced as early as possible to achieve maximum neuroprotection and edema blocking effect. Endovascular cooling has the benefit of shorter time to reach target temperature but catheter insertion requires expertise and trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…MIH involves the rapid application of mild hypothermia regimens, as suggested and confirmed by several recent studies (Brain Trauma Foundation et al, 2007;van der Worp et al, 2007;Song and Lyden, 2012;Urbano and Oddo, 2012). In a study of 1626 patients with severe TBI, suggested that hyperthermia following TBI was a key detrimental factor to patient prognosis, accentuating delayed mechanisms that follow initial physical disruption during the primary injury and causing injury to hippocampal tissues.…”
Section: Figmentioning
confidence: 95%
See 1 more Smart Citation
“…MIH involves the rapid application of mild hypothermia regimens, as suggested and confirmed by several recent studies (Brain Trauma Foundation et al, 2007;van der Worp et al, 2007;Song and Lyden, 2012;Urbano and Oddo, 2012). In a study of 1626 patients with severe TBI, suggested that hyperthermia following TBI was a key detrimental factor to patient prognosis, accentuating delayed mechanisms that follow initial physical disruption during the primary injury and causing injury to hippocampal tissues.…”
Section: Figmentioning
confidence: 95%
“…In addition, Ab may also be responsible for abnormal and potentially adverse metabolic activities, such as low glucose levels, elevated neuronal excitability, oxidative stress in various tissues, intracellular calcium imbalance, and promotion of inflammatory response processes (Lindholm et al, 2006). Therapeutic hypothermia induced by either surface or endovascular cooling in clinical settings has been proven to exhibit both neuroprotective and edema blocking effects following cerebral ischemia (Song and Lyden, 2012). More recently, mild induced hypothermia (MIH) has also been shown to significantly reduce the incidence of SBI (van der Worp et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Brain ischemia remains a major health concerns in the US, but unfortunately few effective and safe treatments are available [2]. Therapeutic hypothermia and thrombolysis with tissue plasminogen activator (tPA) are the only recommended treatments to improve neurological outcomes [6]. However, due to narrow therapeutic time windows (e.g., <3 h for tPA), only few patients can receive treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…9 Conversely, therapeutic hypothermia has long been believed to be capable of reducing primary brain injury and preventing secondary inury, 10 and its use even in stroke patients is an area of ongoing study and scientific interest without definitive conclusions. 11 Therapeutic hypothermia is theorized to combat global ischemia in several unique ways. Global ischemia, defined as perfusion less than a twentieth of the baseline, induces selective neuronal death indicated metabolic acidosis and yielded a pH of 7.30, PCO 2 of 35.0 mm Hg, bicarbonate level of 16 mEq/L, and PO 2 of 390 mm Hg.…”
Section: Case Reportmentioning
confidence: 99%